Xiao Long Bao Fusion with Indonesian Cuisine - Juliana, Juliana; Oei, Jonathan; Carven, Carven; Horn, Nyoman Damien (International Journal of Social and Management Studies, 2022)
The paper is made to research the classic Chinese dish Xiao Long Bao and test if it can work when fused with Indonesian cuisine. This research uses experiments done by giving questionnaires for the respondents to test the quality of the products are good enough and the comparison of each of those products towards each other through various categories. This research is made in the hopes that it can introduce more people towards Indonesian cuisine through the classic Chinese dish and to test the likeability of the dish in different terms such as aroma, taste, texture and appearance. This research is done by creating 4 Indonesian dishes being Soto Ayam Lamongan, Soto Betawi, Sop Ikan Batam and Soto Lamongan and substituting the broth used in the classic Xiao Long Bao with those Indonesian cuisines. Sample data collection is done by using the convinience sampling technique. This research uses the organoleptic test which consists of hedonic test and hedonic quality test which tests human sensories and needs to be answered in 4 categories which are aroma, taste, texture and appearance and involves sending questionnaires for the panelists to give their opinions regarding the fusion cuisine after tasting them. The result shows that the fusion cuisine in this research is valid and reliable while also liked by the different panelists who were given the products in the different categories as seen in the results and discussions through SPSS testing and shows that this dish has good enough quality and be able to help spread the word about Indonesia’s cuisine.